THE STRATEGY OF BAD LOANS â€œPANG PADE PAYUâ€ IN VILLAGE CREDIT INSTITUTION IN BULELENG DISTRICT - Sri Ayuni, Ni Made; Novi Budiasni, Ni Wayan (Universitas Pendidikan Ganesha, 2019)
This research was motivated by a phenomenon in the district of Buleleng related to the number of LPD with conditions that are less healthy to jammed has increased. In addition, the number of LPD that are stuck in Buleleng regency is the highest in Bali. The purpose of this study is to determine the implications of the internal control system and credit policy on the credit settlement strategy, the settlement of bad loans is settled by the principle of ?Pang Pada Payu?. The number of samples in this study were 60 LPD selected based on the stratified random sampling method. The data analysis technique used in this study was a structural equation model (seminal structural modeling) based on variance or component based sem with smartpls 3.0 analysis tools. Based on the results of testing the internal control system has a significant positive effect on the strategy of settlement bad loans ?Pang Pade Payu? Bad Loans Strategy in LPD in Buleleng Regency. Both credit policies have a significant positive effect on the strategy of settlement bad loans ?Pang Pade Payu? Bad Loans Strategy in Village Credit Institutions in Buleleng Regency.